The Relationship Between Resilience And Family Social Support With Psychological Distress In The Cancer Community At RRS (Reach To Recovery Surabaya) - Utomo, Yogi; Suroso; Pratitis, Niken Titi (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to analyze the relationship between resilience and family social support with psychological distress in the breast cancer community at Reach to Recovery Surabaya (RRS). The study utilized a quantitative approach with multiple linear regression analysis. The results revealed that resilience and family social support had a significant negative influence on psychological distress. Resilience showed a coefficient of -0.528 (p = 0.000), while family social support showed a coefficient of -0.648 (p = 0.000). The contribution of these variables to psychological distress accounted for 49.9% (R² = 0.499). These findings indicate that individuals with high resilience and strong family social support are better equipped to manage psychological pressure. Emotional and practical support from families, along with adaptive capabilities, help individuals effectively cope with emotional challenges. This study offers insights for developing psychological interventions focused on enhancing resilience and family social support to improve the psychological well-being of cancer patients.